2014
DOI: 10.1007/s00705-013-1943-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China

Abstract: The etiological role of human papillomavirus (HPV) in cervical cancer has been well established. However, it is inconclusive whether HPV plays the same role in esophageal carcinogenesis. In this study, we detected HPV infection in 145 frozen esophageal tissues, including 30 normal epithelium (ENOR), 37 dysplasia (DYS) and 78 invasive squamous cell carcinoma (ESCC), and in 143 frozen cervical tissues composed of 30 normal epithelium (CNOR), 38 intraepithelial neoplasia (CIN) and 75 invasive squamous cell carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…The HPV positivity rate of 168/189 observed in the present study is atypically high, comparing with previous studies in esophageal cancer (10,18). This result indicated that the prevalence of HPV infection for esophageal cancer in the Tangshan area, and, taken in combination with previous studies (6-10), evidence indicates HPV may serve an etiological role in esophageal cancer.…”
Section: Discussionsupporting
confidence: 72%
“…The HPV positivity rate of 168/189 observed in the present study is atypically high, comparing with previous studies in esophageal cancer (10,18). This result indicated that the prevalence of HPV infection for esophageal cancer in the Tangshan area, and, taken in combination with previous studies (6-10), evidence indicates HPV may serve an etiological role in esophageal cancer.…”
Section: Discussionsupporting
confidence: 72%
“…The incidence of cervical cancer was estimated about 8.7/100, 000 in females and accounts about 6.3% of all female cancer in China (Kim et al, 2009;Guo et al, 2012;Wangesophageal SCC (ESCC) and cervical SCC (CSCC) have similar multi-stage histopathological progression pattern: from normal mucosa to dysplasia, carcinoma in situ, and invasive carcinoma. Moreover, the predilection site of both ESCC and CSCC is the junction of the squamous and columnar epithelium (Liu et al, 2014). Those similarities supported that common environment risk factors might have etiologic effect on both ESCC and CSCC.…”
Section: Introductionmentioning
confidence: 71%
“…Furthermore, the HPV as oncogenes or co-factors in the carcinogenesis of EC has been reported in the last 30 years (Petrick et al, 2014), especially combinative study of HPV infection rate on EC and cervical cancer tumor samples in geographic areas with a high incidence of EC (Zhang et al, 2010;Liu et al, 2014). According to epidemiologic classification, at least 15 oncogenic HPV types were found in cervical precancerous lesions and carcinoma, of which HPV16 and HPV18 were the most prevalent high-risk types worldwide, whereas HPV-58 has been found in a relatively higher proportion in eastern Asia .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, eight studies were excluded because of the limited number. In total, we included 26 eligible studies in the meta-analysis (Cao et al, 2005;Yang et al, 2005;Dai et al, 2007;He et al, 2007;Shuyama et al, 2007;Zhou et al, 2007;Chen et al, 2008;Li et al, 2008;Liu et al, 2008;Lu et al, 2008;Zhao et al, 2009;Liu et al, 2010;Koshiol et al, 2010;Wang et al, 2010;Ayshamgul et al, 2011;Han et al, 2011;Zhang et al, 2011;Guo et al, 2012;Hu et al, 2012;Qu et al, 2012;Liu et al, 2013;Zhang et al, 2013;Cui et al, 2014;Liu et al, 2014).…”
Section: Resultsmentioning
confidence: 99%